School Autonomy and Accountability in Context : Application of Benchmarking Indicators in Selected European Countries - Arcia, Gustavo; Patrinos, Harry; Porta, Emilio; Macdonald, Kevin (World Bank, Washington, DC, 2015)
School autonomy and accountability are two components of School-Based Management (SBM) that complement each other to increase the operational and pedagogical efficiency of schools. If schools have enough operational autonomy to manage their financial and human resources, then they can become accountable to their clients, namely their students and their families and, as a result, increase the probability of improving student learning (Barrera, Fasih and Patrinos, 2009). Since SBM encompasses diverse practices and policies applied in different forms in many countries in the world, the World Bank has initiated the design of SBM indicators that could be of use to governments to identify and implement practices and policies that increase autonomy and accountability and, by inference, induce the education system to produce better learning outcomes (World Bank, 2007; Patrinos, 2010).